Prototyping of an Automation System for Hydroponic Strawberry Nutrient Dosing - Fiosa Putra; Aris Nasuha (Journal of Robotics, Automation, and Electronics Engineering, 2023)
Strawberries are a fruit that is a superior commodity in growing the economy in Indonesia. However, there was a decline in strawberry production from 2017 to 2021. This was due to constraints in the conventional cultivation process and environmental controls that were not yet optimal. This research focuses on designing an automated system for cultivating strawberries in containers using several sensors. The sensors used are the EC sensor to measure hydroponic nutrient levels, the pH sensor to measure water acidity, and the DHT22 sensor to measure temperature and humidity. Sensor data is sent to the server using IoT technology. Data is also visualized through an Android application that can be monitored from anywhere and at any time. The design of the automation system, named Amanda Mini, delivers the right amount of nutrients so that the health and nutrition of strawberry plants are sufficient. Water flow is carried out automatically using water supply pumps, sample pumps, stirrer pumps, and plant pumps. In this way, the Amanda Mini automation system facilitates hydroponic strawberry cultivation activities, which can increase strawberry production.